2018
DOI: 10.1136/esmoopen-2018-000440
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the development of brain metastases in patients with HER2-positive breast cancer

Abstract: BackgroundPatients with metastatic human epidermal growth factor receptor 2-positive breast cancer (HER2+ BC) frequently experience brain metastases (BM). We aimed to define risk factors for the development of BM in patients with HER2+ BC and to report on their outcome.MethodsThis is a retrospective analysis of patients diagnosed with HER2+ BC between January 2000 and December 2014 at Institut Jules Bordet, Belgium. Statistical analyses were conducted with SAS V.9.4 using Kaplan-Meier method and Cox regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 34 publications
0
42
1
Order By: Relevance
“…The study conducted by Hung et al [14] revealed that patients ≤ 35 years tended to develop cerebral lesions in patients with breast cancer. Maurer et al [15] showed that age ≤ 40 years was a risk factor for BM in patients with HER2-positive breast cancer. Our results demonstrated that younger patients were prone to developing brain metastases, which was similar to previous speculations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study conducted by Hung et al [14] revealed that patients ≤ 35 years tended to develop cerebral lesions in patients with breast cancer. Maurer et al [15] showed that age ≤ 40 years was a risk factor for BM in patients with HER2-positive breast cancer. Our results demonstrated that younger patients were prone to developing brain metastases, which was similar to previous speculations.…”
Section: Discussionmentioning
confidence: 99%
“…Schovanek et al [16] suggested that 4.5 cm was the optimal cut-off primary tumor size which can predict development of any metastases from pheochromocytoma/paraganglioma. Maurer et al [15] identified tumor size > 2 cm as a risk factor for the development of BM in patients with HER2-positive breast cancer. Sun et al [7] revealed that white/other race, clear cell histology, sarcomatoid differentiation, T2-4 disease, tumor dimension > 10 cm, and N+ disease were risk factors of BM development at RCC diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the general BC population, the effect of age on the risk for BCBM in TNBC and HER2-positive patients was not as prominent. Five studies reported a statistically significant multivariable association between young age and risk for BCBM with effect estimates ranging between 1.66 -2.7 [17,25,26,44,80], whilst no significant association was found in the rest of the studies considering solely HER2-positive patients, likely reflecting the small sample size used [20, 23-25, 61, 81]. Similarly, in the subset of studies involving TNBC patients, age was not found to impact BCBM [24,39,71].…”
Section: Agementioning
confidence: 96%
“…High primary tumor histological grade (G3 vs. G1-2) was recurrently associated with BCBM progression, with twelve [19,28,29,36,38,51,52,57,59,70,78,79] of the 19 studies examined [12, 16, 19, 28, 29, 33, 36, 38, 40, 50-53, 57, 59, 70, 72, 78, 79], reporting a statistically significant univariate association. On multivariate analysis, a significant positive association between Grade 2 [26,80] 5 NR, p < 0.05 [17]; <50 years, HR: 2.7, p = 0.0048 [25]; ≤50 years, HR: 1.92 p = 0.04 [26]; Young age OR: 1.66 p = 0.014 [44]; ≤40 years, p = 0.045 [80] Hormone receptor status 7 [20,26,27,44,61,66,80] 3 [20,44,66] 2 Negative, OR: 1.75 p = 0.033 [44]; Negative, RR: 3.41 p = 0.01 [ [17,23,24,44,47,61] 2 [47,61] 3 OR:1.61 p = 0.025 [80]; Late (≥6 months after BC diagnosis), HR: 2.65, p = 0.043, No, HR:3.79, p = 0.0042 [44]; ≥2 line OR: 3.43 p = 0.003 [61] HR -Hazard Ratio; OR -Odds Ratio; RR -Relative risk; NR -Not Reported.…”
Section: Primary Tumor Gradementioning
confidence: 99%
See 1 more Smart Citation